Potential Echinodermata in Samboang Beach Bulukumba District as a Source of Biodiversity Learning - Angraeni, Andi Tirta; Arsal, Andi Faridah; Saleh, Andi Rahmat (Universitas Negeri Makassar, 2024)
This research aims to find out what echinodermata can be found on Samboang Beach in Bulukumba district that can be used as a source of learning outside the classroom. This research uses a type of qualitative descriptive research. The research instruments used in this study are the observation sheet and identification sheets. Based on observations and data identification, it can be concluded that